2021
DOI: 10.3389/fcell.2021.732204
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition and Fecal Metabolic Profiling in Patients With Diabetic Retinopathy

Abstract: Recent evidence suggests there is a link between metabolic diseases and gut microbiota. To investigate the gut microbiota composition and fecal metabolic phenotype in diabetic retinopathy (DR) patients. DNA was extracted from 50 fecal samples (21 individuals with type 2 diabetes mellitus-associated retinopathy (DR), 14 with type 2 diabetes mellitus but without retinopathy (DM) and 15 sex- and age-matched healthy controls) and then sequenced by high-throughput 16S rDNA analysis. Liquid chromatography mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 62 publications
(63 reference statements)
1
26
1
Order By: Relevance
“…Analysis of microbiota composition showed a significant decrease in the percentage of Pasteurellaceae in DR patients ( 12 ). At the genus level using high-throughput 16S rDNA analysis, Faecalibacterium , Roseburia , Lachnospira , and Romboutsia were enriched in DR patients ( 16 ). The 16S rRNA gene sequencing and untargeted metabolomics showed that reduced diversity and altered composition of gut microbiota and specific microbe–metabolite interplay were associated with proliferative DR ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of microbiota composition showed a significant decrease in the percentage of Pasteurellaceae in DR patients ( 12 ). At the genus level using high-throughput 16S rDNA analysis, Faecalibacterium , Roseburia , Lachnospira , and Romboutsia were enriched in DR patients ( 16 ). The 16S rRNA gene sequencing and untargeted metabolomics showed that reduced diversity and altered composition of gut microbiota and specific microbe–metabolite interplay were associated with proliferative DR ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 11 ) reported that restructuring of the gut microbiome by long-term intermittent fasting prevented the development of DR and prolonged the life span by activation of tauroursodeoxycholate (TUDCA) receptor (TGR5) in a diabetic db/db mouse model. The recent focus on gut microbiome dysbiosis in DR patients has led to new pathophysiological and therapeutic directions ( 12 16 ). Most of these microbiome studies regarding DR used 16S rRNA sequencing, which limited their associations in the microbiome to the genus level.…”
Section: Introductionmentioning
confidence: 99%
“…The data were preprocessed for further analysis as follows: filtering merged Raw Tags to get high-quality Clean Tags by software Trimmomatic v0.33; identifying and removing chimeric sequences to get Effective Tags by software UCHIME v4.2. The data analysis method was described previously ( Zhou Z. et al, 2021 ; Lin Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Resident bacterial species in the gut can also influence free amino acid distribution in the gastrointestinal tract ( 28 ). In addition, multiple studies have pointed to a causal relationship between gut microbiome dysbiosis and T2D, found that there is dysregulation of the gut microbiota in DR patients with diabetes,and DR patients exhibited enrichment of gut microbiota components at the genus level ( 29 31 ).After studying of T2D complications, it is found that the significant differences in gut microbiota composition not only between the DR and healthy groups, but also between the DR and T2D groups ( 29 ). Gut microbiota, not only worked in amino acids metabolism, but also in several other process, one of the most important is the modulation of the sensitivity to peripheral insulin.…”
Section: Discussionmentioning
confidence: 99%